Investigating Translatability and Translation Strategies of Idiomatic Expressions in the Blind Owl by Hedayat Analyzing the Native Translator’s Performance - Maryam Niami; Farzaneh Akar (LANGUAGE ART, 2023)
The globalization of communication has increased the importance of translation. However, sometimes cultural and linguistic differences between languages are challenging even more than the translator’s role. Idiomatic expressions are often challenging issues in the realm of translation. This article has investigated applied strategies and translatability of idiomatic expressions in The Blind Owl (Būf-e kūr). Therefore, the well-known English translation by Bashiri (2013) was examined. The data were analyzed to find applied strategies and investigate the translatability and untranslatability of idiomatic expressions. Two hundred ninety idiomatic expressions were collected of the corpus and its English translation. A few untranslatable idiomatic expressions have been found due to linguistic and cultural differences. Moreover, the author’s style in the book has impacted the translation. Although Bashiri’s performance as a native translator in applying translation strategies was found efficient, in some cases, his familiarity with the language and culture of the source language does not lead to total correspondence between the source and target texts.